Humanistic health of the physical living environment: The equity of property inheritance in China - Shu, Mengrong; Li, Jinxin; Wu, Yuhan; Chen, Kaida; Ding, Shuhui (Frontiers in Public Health, 2023)
Equity in the inheritance culture of family property is an important component of humanistic health in modern living environments. The inheritance of property under Chinese traditional family culture is the material basis for the continuation of family and clan. This study demonstrates the equity component embedded in traditional family inheritance culture and further studies the health of the human settlements environment. The author chose Renhe Village, a typical local residential building of the middle and late Qing Dynasty in Yongtai, Fujian Province, to evaluate and discuss equity. Based on the investigation, a building data model was established with space syntax and 3D simulation technology to carry out simulation analysis of space and climate, thereby building a traditional residential equity evaluation system based on the natural unit indicator and the overall spatial indicator. The results show that the natural unit indicator interprets the equity of room quantity ratio using three evaluation indices: quantity, lighting, and ventilation. However, overall spatial indicators consider the balance of space distribution through the indices of privacy, centrality, and convenience. It is also found that the standard of evaluating equity is not the absolute average of measurements, but the mutual balance of six indices under the dual indicators. Based on the above, an equity system model of housing property rights distribution was established, and the weight of the ancients’ attention to the housing distribution standard was explored. These findings enrich and deepen the connotation of humanistic care in living environments and provide new ideas for understanding the equity of property inheritance under Chinese traditional family culture. They generate a new perspective for in-depth analysis of the spatial form and fabric of traditional residential buildings, as well as the internal cultural logic, providing a reference for the humanistic public health of the modern living environment, and ultimately exploring a sustainable development model for contemporary Chinese villages based on heritage values.